Parents Knowledge of Oral Health of Children with Cancer - Omar, Hinda Khaleel; Muttaleb, Wisam Mashaan (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): To assess parents' knowledge about oral health for their children with cancer.Methods: A descriptive study design conducted among 110 parents of children diagnosed with cancer. The study started from 1st July 2022 to 31 March 2023 at Baquba Oncology Center in Diyala, Iraq. Data was collected using Oral Health Scale (A-OHAT), and participants sociodemographic data. The self-report strategy was adopted to collect data from the participants. Data were analyzed through the use of the SPSS version (26).Results: Parents have a high level of knowledge regarding the oral health for their children with mean score 2.58. However, they showed a moderate level in teeth eruption and dental distortion knowledge with mean score (2.11, 1.93) respectively. In spite of high percentage of parents have inadequate educational level.Conclusion: Parents have adequate levels of knowledge regarding oral health care for their children with cancer.Recommendations: A follow up and routine oral exam for cancer child, planning educational oral health programs to develop parents awareness on subjects related to oral health. Exam oral habits and behaviors practices of pediatric oral care.